Effects of a programme to advance scholarly writing. (3rd December 2018) - Rohan, Annie; Fullerton, Judith
Summary: Background: Scholarly writing, although central to the completion of doctoral studies, is often not supported by systematic teaching/learning approaches that specifically help students to convey scholarship through writing. The purpose of this project was to promote writing as an essential component of scholarship, provide opportunities for students to develop a self‐awareness of confidence in writing and challenges to writing, and to improve writing competence. Methods: An innovative set of peer‐supported interventions was embedded within a core foundational course in a Doctor of Nursing Practice (DNP) programme during the first academic semester as part of a continuing quality improvement process to improve DNP student writing. The first curriculum innovation was a substantive writing assignment, in which students exchanged papers with a classmate and were required to critique both writing conventions (e.g. criteria such as punctuation and citation) and structural and thesis‐driven aspects of writing (e.g. criteria such as clarity, organisation and the use of paragraph leading sentences). Students then read their papers aloud, without hesitation while reading, in order to identify any discrepancies between the written words and the audible 'plain language' that would be necessary to enhance clarity. The second innovation was an optional writing workshop in which students received coaching from interdisciplinary mentors and from their peers. Results: Evaluation of the implementation of this innovation suggests that mentorship, peer support and the use of commonly spoken language may be useful tools for improving the writing competencies of DNP students. Discussion: Students with broad diversity in writing competency, including low levels of proficiency, benefitted from a writing‐enriched curriculum given at the start of the course of study. DNP faculty may not themselves be prepared to mentor students for doctoral‐level writing